2021
DOI: 10.1556/066.2020.00178
|View full text |Cite
|
Sign up to set email alerts
|

Social media and unhealthy food nexus: Evidence from Saudi Arabia

Abstract: This study assesses consumers' preference for food from social media on a sample of 510 respondents from the Eastern region of Saudi Arabia using the Best-Worst Scaling method. The findings of the study conclude that unhealthy and nutrient-poor food items are more preferred than healthy and nutrient-rich food items. The study recommends that the food and drug authority should intervene to increase consumers' awareness about the effect of unhealthy food items by creating social media accounts to warn consumers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…While Facebook was the most frequently used social media site in Saudi Arabia in 2011, it lost this position to Twitter in 2013 [42]. Moreover, a 2021 study conducted in Saudi Arabia showed that Snapchat, Twitter, Instagram, and YouTube were the most desired social media platforms [43], which is consistent with this study's findings.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…While Facebook was the most frequently used social media site in Saudi Arabia in 2011, it lost this position to Twitter in 2013 [42]. Moreover, a 2021 study conducted in Saudi Arabia showed that Snapchat, Twitter, Instagram, and YouTube were the most desired social media platforms [43], which is consistent with this study's findings.…”
Section: Discussionsupporting
confidence: 86%
“…Food and drink marketing on social media platforms has a powerful influence on eating habits among young populations [44]. Because young adults usually spend more time browsing the Internet, own personal smartphones, and are registered on more than one social media channel, they are heavily exposed to food and drink advertisements, especially in comparison to other forms of marketing [43,44]. In this study, the participants generally had high exposure to food and drink marketing via social media platforms, with about half reporting exposure three to four times per day, and one-quarter reporting once per day during the last month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study conducted among university students in Saudi Arabia showed that participants who purchased foods/drinks more frequently after viewing such ads consumed higher amounts of potato chips and fast foods [ 22 ]. According to a study by Aldossari and Al-Mahish (2021) that focused on social media preferences for determining Saudi Arabian residents’ eating habits, the majority of respondents preferred unhealthy and nutrient-poor food products over healthy and nutrient-rich food [ 23 ]. In addition, there is evidence of the impact of social media influencers on food consumption among the Saudi population [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the research studies in Saudi Arabia focused on the social media applications in health management from different perspectives. For instance, Aldossari and Al-Mahish study (24) focused on the used social media preferences for determining the food habits of the Saudi Arabian residents and found that the majority of the people preferred unhealthy and nutrient-poor food items over healthy and nutrient-rich food. Similarly, Al-Hamdan et al (25) investigated the use of social media (WhatsApp) as an intervention for educating and creating health awareness among Saudi females with prediabetes and found that the application was significant in creating awareness and creating behavioral change, resulting in improved HbA1c levels.…”
Section: Introductionmentioning
confidence: 99%